2019
DOI: 10.2217/fvl-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Study of the Influenza a Virus M2 Protein and Aluminum Salt Adjuvant Interaction As a Vaccine Candidate Model

Abstract: Aim: The present study evaluated the structural changes resulting from the interaction between a recombinant influenza A virus M2 protein and aluminum hydroxide adjuvant to investigate the antigen for further immunological studies. Materials & methods: Membrane protein II was produced from the H1N1 subtype of human influenza A virus. The interaction between M2 protein and alum inum hydroxide adjuvant was evaluated by physicochemical techniques including scanning electron microscope, UV-Vis spectra, Fourier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…A study has shown that genetic susceptibility induces central nervous system damage following alum-adjuvanted vaccines [31,33,36]. Most of these side effects might be related to altering the protein's epitope folding in contact with aluminum [37]. In addition to the toxic effects of alum on the nervous system, it can increase the level of IgE by increasing the cellular immune responses (Th2) and lead to the allergies in people, especially susceptible children [38].…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that genetic susceptibility induces central nervous system damage following alum-adjuvanted vaccines [31,33,36]. Most of these side effects might be related to altering the protein's epitope folding in contact with aluminum [37]. In addition to the toxic effects of alum on the nervous system, it can increase the level of IgE by increasing the cellular immune responses (Th2) and lead to the allergies in people, especially susceptible children [38].…”
Section: Discussionmentioning
confidence: 99%